Research protocol for bridging research, accurate information and dialogue (BRAID)—clinical trials: a mixed-methods study of a community-based intervention to improve trust and diversify participation in clinical trials - Gutnick, Damara N.; Lozano, Patricia; Rodriguez Martinez, Smeily; Wang, Katherine W.; Williams, Debra A.; Rapkin, Bruce D.; Gonzalez-Lepage, Nelly (Frontiers in Public Health, 2024)
Cultural beliefs, personal experiences, and historic abuses within the healthcare system-rooted in structural racism-all contribute to community distrust in science and medicine. This lack of trust, particularly within underserved communities, contributes to decreased participation in clinical trials and a lack of representation in the data. Open dialogue about community concerns and experiences related to research participation and medical care processes can help build trust and change attitudes and behaviors that affect community health. This protocol outlines an approach to increase trust in science and clinical trials among communities in the Bronx, New York that are typically underrepresented in research data. Bridging Research, Accurate Information and Dialogue (BRAID) is a two-phased, evidence-based community engagement model that creates safe spaces for bilateral dialogues between trusted community messengers, and clinicians and scientists. The team will conduct a series of BRAID Conversation Circles on the topic of clinical trials with local trusted community messengers. Participants will be members of the community who are perceived as "trusted messengers" and can represent the community's voice because they have insight into "what matters" locally. Conversation Circles will be audiotaped, transcribed, and analyzed to identify emergent challenges and opportunities surrounding clinical trial participation. These key themes will subsequently inform the codesign and co-creation of tailored messages and outreach efforts that community participants can disseminate downstream to their social networks. Surveys will be administered to all participants before and after each Conversation Circle to understand participants experience and evaluate changes in knowledge and attitudes about clinical trials, including protections for research participants the advantages of having diverse representation. Changes in motivation and readiness to share accurate clinical trial information downstream will also be assessed. Lastly, we will measure participants dissemination of codesigned science messages through their social networks by tracking participant specific resource URLs of materials and videos posted on a BRAID website. This protocol will assess the effectiveness and adoptability of an innovative CBPR model that can be applied to a wide range of public health issues and has the potential to navigate the ever-changing needs of the communities that surround health systems.